Modelling atmospheric pollution during the Games of the XXVIII Olympiad: Effects on elite performers - Flouris, A. D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Regardless that voluminous literature has appeared about the detrimental effects of atmospheric pollution on a number of exercise-performance aspects, world-wide athletic meetings such as the Olympic Games must, inevitably, be held in large metropolises. As the Opening Ceremony of the XXVIII Olympiad is upon us, a comprehensive analysis of the potential atmospheric conditions in Athens during the summer of 2004 is of considerable value. Methods Olympic competition venues are spread in the greater Athens area (GAA) at sea-level atmospheric pressure and 850 hPa geopotential height at 315 grid points in an area confined by the 25° N and 60° N parallels and the 10°W and 40° E meridians spaced by 2.5°. Atmospheric pollution and weather data for the period April 16th . September 30th covering the entire GAA and collected from 1984 to 2003 were used for descriptive statistics and model fitting. The analysis was focused on carbon monoxide (CO), ozone (O3), sulfur dioxide (SO2), nitrogen oxides (NOx), and particulate matter with a diameter of <10 Makrometer (PM10). Results Results suggest that athletes will mainly experience the adverse effects of O3, SO2, and PM10 (mean 2002 values: 69.9 +/- 4.3, 48 +/- 1.9, 60 +/- 3.6 Makrog/m3, respectively). Concentrations of CO, NO, and NO2 have remained consistently low during the past decade (mean 2002 values: 5.3 +/- 1.1 mg/m3, 110 +/- 7.8, and 98 +/- 5.1 Makrog/m3, respectively). O3 presents its maximum values in the northern sector of the city, followed by the southern and central sectors (P<0.05). The equivalent for CO, NOx, and PM10 is central, southern, and northern sectors, while for SO2 this sequence is southern, central, and northern sectors (P<0.05). O3, and NO2 present their highest values during days of increased incoming solar radiation, temperature, and very weak southern wind flow (P<0.05). In contrast, NO, CO, SO2, and PM10 present their maximum values during days of reduced horizontal advection and increased cloudiness (P<0.05). The highest concentration of all pollutants is noted in the morning (7-11am) and during the night (9-11pm) (P<0.05), with similar kinetics during all seven days of the week (P>0.05). It is also important to note that June, July, and August represent months with the highest number of days (P<0.05) during which atmospheric pollution in Athens was above the air quality standards imposed by the European Union. Correcting for changes in temperature and population dense, general linear model framework incorporating generalized estimated equations approximated mean August 2004 pollutant concentrations similar to: CO: 7mg/m3, O3: 74, SO2: 55, NO: 118, NO2: 105, and PM10: 73 Makrog/m3. Accurate pproximations of specific daily air quality conditions will be possible at least three days in advance. Discussion/Conclusion The adverse effects of O3, SO2, and PM10 on submaximal and maximal exercise have been well documented (Cedaro, 1992; Carlisle & Sharp, 2001). O3 exposure in heavily exercising individuals may attenuate performance, primarily due to discomfort caused by changes in pulmonary function. In the case of elite athletes or asthmatics, these symptoms are exacerbated at even low concentrations (i.e. 24 Makrog/m3). Exposure to SO2 produces effects similar to O3, by acting as an airway irritant. SO2 can impair ventilation by transiently increasing resistance in the upper respiratory tract via the stimulation of subepithelial receptors in the larynx, tranchea, and bronchioles by vagal nerve mediated constriction of the rerespiratory tree of. While the transient exposure of Olympic athletes to PM10 is unlikely to affect exercise performance, it may have significant effects on health as the increased airflow velocity during exercise bypasses much of the normal nasal filtration and carries pollutants deeper into the respiratory tract. Medications that may alleviate the effects of O3 exposure include apocynin (Peters et al., 2001), while the adverse effects of exposure to SO2 and PM10 may be attenuated by most general asthma treatments (e.g. beta-agonists). Precaution measures discussed by the Olympic Organizing Committee include limitation of car use and industrial productivity in the GAA for the duration of the Olympic and Paralympic Games. Precaution measures must be also adopted by national teams, especially in the case of asthmatic athletes, to minimize the potential hazards encountered when training and competing in such adverse atmospheric conditions.